Living/Listening as If the Gospel Is True. Issue 3 (October 2022) - Mather, Michael
The Missing Voices Project could be named the Missing Listeners Project. The voices of the very young are present, but there aren't practices that pay attention to their voices. How will the adults in congregations and ministries pay attention to the gifts, prophecies, talents, passions, and work of the young people that surround them? Listening to the adults and young people in the Missing Voices Project invites us to join God's good work in the world.